Tinjauan Yuridis Penggolongan Penduduk Dalam Pembuatan Keterangan Waris - Sari Elsye Priyanti (Lex Renaissance, 2019)
This study examines the classification of indigenous and non-indigenous populations in formulating the information regarding the heir from the perspective of eliminating racial and ethnic discrimination. There are two main issues raised in this study, firstly, whether the population classification in Perkaban No. 3 of 1997 in accordance with Law No. 40 of 2008 on the Elimination of Racial and Ethnic Discrimination. Secondly, whether the difference between the authorities in providing the certificate of inheritance according to Perkaban No. 3 of 1997 can provide legal certainty. This research is a normative juridical study with a statutory approach. This study concluded that, first Article 111 of Perkaban No. 3 of 1997 concerning the classification of the population in the making of a certificate of inheritence contrary to Law No. 40 of 2008 on the Elimination of Racial and Ethnic Discrimination. Second, the difference between the authorities giving the certificate of inheritance according to Perkaban No. 3 of 1997 has guaranteed legal certainty, as Perkaban No. 3 of 1997 specifically regulates the certificate of inheritance. However, this regulation still needs improvement in the future.